Discrete asymptotic homomorphisms in E-theory and KK-theory - Thomsen, Klaus (Mathematica Scandinavica, 2003)
We obtain six-term exact sequences for E-theory and KK-theory which involve discrete asymptotic homomorphisms and generalize the extension of groups from the UCT theorem.